Hubungan Pola Makan dengan Indeks Massa Tubuh pada Santri/Santriwati - Latifah Azmy Nasution; Delfriana Ayu A (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: Nutrition problem is a global health problem that requires special attention. In Indonesia, the problem of nutrition has not been completely resolved. Nutritional problems are related to a person's diet. This study aims to determine the relationship between diet and body mass index of students at the At-Taufiqurrahman Islamic Boarding School. Methods: This type of research is quantitative analytic with a cross sectional research design. The population is 61 people, the sample of this study is 61 people. The sampling technique is total sampling. Instruments in this study are questionnaires or questionnaires, weight scales and microtoise. Analysis of the data used is descriptive analysis and Spearmen Test. Results: The results showed that there was a significant relationship between diet (amount of energy (p = 0.001), amount (protein p = 0.001), type of food (p = 0.015) and the body mass index of students at Pondok Pesantren At Taufuqurrahman. Conclusion: There is a relationship between diet and body mass index of students at the At-Taufiqurrahman Islamic Boarding School. It is hoped that the pesantren will pay more attention to the food menu consumed by students.